L‒asparaginase activity in some endophytic fungi: Glutaminase‒free and low urease co‒activities - Zahra Zaeimian; Khalil-Berdi Fotouhifar; Mohsen Farzaneh (PLoS ONE, 2026)
In this study, L‒asparaginase production in several endophytic fungi was evaluated along with their L‒glutaminase and urease co-activities. The effect of L‒asparagine and different culture media on L-asparaginase production were also evaluated. Among the 62 investigated isolates, 49 isolates exhibited L‒asparaginase activity, and the maximum zone index (6.58) was observed in Cladosporium perangustum EL1. Evaluation of L‒glutaminase and urease co-activities in L‒asparaginase-positive isolates screened 19 isolates with no L‒glutaminase activity and four isolates with minimum urease production. L‒asparaginase activity was quantified in 12 selected isolates using the Nesslerization method. Cladosporium cladosporioides Kr5−2 exhibited the maximum L‒asparaginase activity (10.78 U mL -1 ). Alternaria brassicae C showed high L‒asparaginase activity (7.07 U mL -1 ) free of L‒glutaminase, and low urease co-activity (1.97 U mL -1 ). Assessment of the effect of L‒asparagine on L‒asparaginase activity showed that the enzyme is inducible and substrate-regulated. Evaluation of ten different culture media showed that all isolates were able to produce L‒asparaginase on Mineral salts agar and Citrate agar culture media. Also, Cerelose ammonium nitrate agar, Kuehner basal culture medium, and Piefer, Humphrey, and Acree culture medium inhibited L‒asparaginase production in the majority of the isolates. This is the first report of L‒asparaginase production by endophytic fungi isolated from Taxus baccata , Pistacia vera , Prunus avium , Prunus cerasus , and Punica granatum , as well as the investigation of their L‒glutaminase and urease co-activities. Among the evaluated culture media, Mineral salts agar and Citrate agar culture media are suggested here as alternate for MCD. Moreover, Alternaria brassicae C is recommended as a promising isolate for future commercial L‒asparaginase production.